2015
DOI: 10.1063/1.4905945
|View full text |Cite
|
Sign up to set email alerts
|

Modeling small-signal response of GaN-based metal-insulator-semiconductor high electron mobility transistor gate stack in spill-over regime: Effect of barrier resistance and interface states

Abstract: We provide theoretical and simulation analysis of the small signal response of SiO 2 /AlGaN/GaN metal insulator semiconductor (MIS) capacitors from depletion to spill over region, where the AlGaN/SiO 2 interface is accumulated with free electrons. A lumped element model of the gate stack, including the response of traps at the III-N/dielectric interface, is proposed and represented in terms of equivalent parallel capacitance, C p , and conductance, G p . C p -voltage and G p -voltage dependences are modelled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…13 Fig. 4 14 indicates that the conventional conductance measurement could underestimate the interface states value. For this reason, two additional electrical evaluations were used: AC-g m dispersion 8,15 and the V TH shift during a positive gate bias stress.…”
Section: Correlation Of Interface States/border Traps and Threshold Vmentioning
confidence: 99%
“…13 Fig. 4 14 indicates that the conventional conductance measurement could underestimate the interface states value. For this reason, two additional electrical evaluations were used: AC-g m dispersion 8,15 and the V TH shift during a positive gate bias stress.…”
Section: Correlation Of Interface States/border Traps and Threshold Vmentioning
confidence: 99%
“…Recently, we adopted ac-conductance method to characterize the interface traps in Al 2 O 3 (AlN NIL)/GaN MOSC diode (without barrier layer in the gate region) with the same gate dielectric stack process as described in this paper [26]. Similar D it 's ranges in MIS and MOSC diodes extracted, respectively, using ac-capacitance and ac-conductance techniques further validate the effectiveness of ac-capacitance method for interface trap mapping in practical III-N MIS heterostructures, suggesting that ac response of interface traps can make primary contribution to the f /T -dispersions in ac-CV characteristics as long as D it is not extremely low [8].…”
Section: Ac-cv Techniques For Interface Trap Mappingmentioning
confidence: 61%
“…It is because a high density of interface traps at a low-quality interface could pin the Fermi level at a deep level, at which the filling/emission processes of interface traps cannot respond to the ac measurement signal, impeding the presence of second rising slope in the measured ac-CV characteristics of III-N MIS heterostructures. Recently, Capriotti et al [8] reported that the ac response of interface traps and the barrier layer could result in comparable effects on the second rising slope when the interface trap density is extremely low (in the order of 10 11 cm −2 ), but the ac response of interface trap still dominates over that of barrier layer as long as interface trap density is higher, which is the case for most III-N MIS heterostructures to date. To explain the physical mechanisms of the second slope in ac-CV characteristics, the response of interface traps to the ac measurement signal v ac need to be analyzed.…”
Section: Ac-cv Techniques For Interface Trap Mappingmentioning
confidence: 95%
See 1 more Smart Citation
“…21,[25][26][27] The method reported by Yang et al 27 f -dispersions of the second slope onset (V ON ) in the ac-CV characteristics (Fig. 2), the interface-state density of LPCVD-SiN x /GaN-cap/AlGaN was calculated by…”
mentioning
confidence: 99%